Impact of Information Sharing and Supply Chain Collaboration on the Perfomance of Herbal SMEs in Batam: The Mediating Role of Innovation Capability - Putri, Anandita Nadya Reisya; Laulita, Nasar Buntu (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study looks at how sharing information and working together in the supply chain affect the performance of small and medium herbal businesses in Batam. It also explores how innovation ability plays a middle role in this relationship. The research used a quantitative method by giving questionnaires to 198 herbal businesses in Batam and analyzing the results using Partial Least Squares Structural Equation Modeling.The results show that information sharing has a significant positive effect on both performance and innovation capability. In contrast, supply chain collaboration and innovation capability do not significantly influence performance, and innovation capability does not mediate the relationship between information sharing or supply chain collaboration and performance. These findings highlight the importance of information sharing in enhancing competitiveness, while collaboration and innovation still require further optimization. Practically, enterprises are encouraged to adopt digital platforms for information sharing and strengthen strategic cooperation with suppliers, while government support is needed through technology and innovation training. This study is limited to Batam with cross-sectional data, suggesting that future research should examine external factors such as digitalization and global market dynamics.